Cetacean strandings in Oregon and Washington between 1930 and 2002 - Norman , S. A.; Bowlby , C. E.; Brancato , M. S.; Calambokidis, J.; Duffield, D.; Gearin, P. J.; Gornall, T. A.; Gosho, M. E.; Hanson, B.; Hodder, J.; Jeffries, S. J.; Lagerquist, B.; et al. (J. Cetacean Res. Manage., 2023)
The Northwest Region (NWR) Marine Mammal Stranding Network was created in the early 1980s to provide a consistent framework in which to collect and compile data about marine mammal strandings in Oregon and Washington. The NWR includes the nearshore waters and 4,243km (2,632 n.miles) of coastline. For the years 1930-2002, there were 904 stranding events, representing 951 individual animals and 23 species: 4 species of balaenopterids, 1 eschrichtiid, 2 physeterids, 4 ziphiids, 10 delphinids and 2 phocoenids. Gender was determined for 343 males and 266 females. Only one mass stranding was recorded (sperm whales: 1979). A few species comprised the majority (71%) of stranding events in the NWR: harbour porpoise (34%), gray whales (23%), Dall’s porpoise (12%) and Pacific white-sided dolphins (4%). There was a steep increase (511%) in the number of stranding reports beginning in the 1980s with over 86% of all records occurring during the last two decades (1980s and 1990s). The general trend of increased reported strandings during the last two decades corresponds to the formation of a formal stranding network and a heightened interest and dedication by the public and government agencies in reporting and documenting strandings. For all events combined, the primary stranding peak was April-July. Since stranding recoveries depend heavily on reports from the general public, most stranding records were in summer when more people are present along the coastline. Individual species or species groups showed varying levels of conformity to this overall seasonal trend. The value and limitations of the use of strandings data in a management context are discussed.